IAU100 Activities and Recent Developments in Turkish Astronomy - Sinan, Alis
In this paper, astronomy activities in Turkey in the year of 2019 are summarized. Especially, public outreach activities and teacher training programs in the framework of IAU100 celebrations are given. Current status of the Eastern Anatolia Observatory and Turkish Space Agency are also summarized. Finally, recently established working group on the legislation for the light pollution is introduced.
Keywords: Astronomy